151k views
1 vote
What is the middle term of the product of (x - 4)(x - 3)?


2 Answers

4 votes

Answer:

Explanation:

= x(x-3) - 4(x-3)

= x²-3x - 4x + 12

= x² -7x +12

So -7x is the middle term

User Fabiopagoti
by
5.0k points
4 votes

Answer:

- 7x

Explanation:

Given

(x - 4)(x - 3)

Each term in the second factor is multiplied by each term in the first factor, that is

x(x - 3) - 4(x - 3) ← distribute both parenthesis

= x² - 3x - 4x + 12 ← collect like terms

= x² - 7x + 12

with middle term = - 7x

User Koitt
by
5.0k points